STEREOTIPE POTRET WANITA DALAM FILM BARBIE OLEH GRETA GERWIG: STUDI SEMIOTIKA: Stereotypes are labels often used by certain people to others (ELATICS JOURNAL, 2024)
Stereotypes are labels often used by certain people to others. One of the stereotypes depicted in the 2023 live-action Barbie film by Greta Gerwig is a woman stereotype. This research aims to describe the practices and signs of stereotypes against women experienced by the character Barbie in the 2023 live-action Barbie film. Stereotypes construct society's perception of women and strengthen the stigma that women tend to be the objects of labeling. Forms of negative labeling are developed from the order of social life internalized by the woman Alone. Negative labeling can have an impact on women's lives. This type of research uses descriptive qualitative methods to obtain information and depict stereotypes experienced by the character Barbie. The data source was taken from the film entitled Barbie Greta Gerwig and uses Halliday's social semiotic theory. Data collection stages Use listening and note-taking techniques to obtain relevant information. Meanwhile, the data research stage uses data analysis techniques. The research finding shows the practice of stereotyping women with negative labeling as women who are less free to speak, more emotional, not likely to appear as a leader, home-oriented, and not very independent a theory from Unger (1979). Keywords: Movie, Semiotics, Signs, Stereotypes.